Youth’s Behaviour Towards Halal Tourism In West Sumatra - Nurul Huda; Nova Rini; Muslikh Muslikh; Zulihar Zulihar (Islam Realitas: Journal of Islamic and Social Studies, 2021)
Research on the behavior of the millennial generation towards halal tourism in Indonesia is still limited This article aims to look at millennial generations' role (especially students) in visit halal tourism in the West Sumatra region. The research method used is quantitative with the sampling technique is purposive sampling, so that the data analyzed is valid. The analytical method used is the Structural Equation Model (SEM) method with SmartPLS software. The number of respondents was 156. This study indicates that the Islamic Religiosity variable significantly influenced millennial attitudes and behaviour in purchasing halal tourism. Meanwhile, the variable of halal tourism knowledge in this study influenced their behaviour significantly. Still, it did not significantly affect their attitudes. Islamic Religious Millennial generation has a significant effect on attitudes toward purchasing halal tourism. Halal knowledge of the millennial generation, Islamic Religious Millenial, and Attitude significantly influences purchasing halal tourism.Penelitian mengenai perilaku millennial terhadap wisata halal di Indonesia masih terbatas. Artikel ini bertujuan untuk melihat peran generasi milenial (khususnya mahasiswa) dalam kunjungan ke wisata halal di wilayah Sumatera Barat. Metode penelitian adalah kuantitatif dengan teknik pengambilan sampel adalah purposive sampling, sehingga data yang dianalisa akan valid. Metode analisa yang digunakan adalah metode Structural Equation Model (SEM) dengan software SmartPLS. Jumlah responden 156. Hasil penelitian ini menunjukkan bahwa variabel Religiusitas Islam berpengaruh signifikan terhadap sikap dan perilaku milenial dalam pembelian wisata halal. Sedangkan variabel pengetahuan pariwisata halal dalam penelitian ini berpengaruh signifikan terhadap perilaku mereka. Meski begitu, hal itu tidak terlalu mempengaruhi sikap mereka. Generasi Milenial Religius Islam berpengaruh signifikan terhadap sikap pembelian wisata halal. Pengetahuan Halal Generasi Milenial, Milenial Religius Islam, dan Sikap berpengaruh signifikan terhadap perilaku pembelian wisata halal.